Exploration of the social determinants of diarrhoea, rotavirus vaccine uptake, and vaccine ‘fatigue’ in Ethiopia, Kenya, and Malawi - Mackwellings Maganizo Phiri; Rahma Osman; Shewit Weldegebriel; Steven Sabola; Beatrice Ongadi; Catherine Beavis; Chikondi Mwendera; Deborah Nyirenda (PLoS ONE, 2025)
Diarrhoea due to rotavirus remains a significant cause of child mortality in developing regions. Caregivers’ perspectives on the social determinants of gastroenteritis and childhood vaccination, including the rotavirus vaccine, were explored through focus group discussions in Ethiopia (n = 6), Kenya (n = 14), and Malawi (n = 10), using a combination of thematic and framework analysis approaches. The results show that diarrhoea was perceived to be a burden in all three countries, particularly among infants, due to challenges in WASH (water, sanitation, and hygiene) infrastructures and poverty. Prevention strategies mentioned by the caregivers focussed on enhancing WASH interventions without mention of vaccination. Participants however expressed a lack of agency to address WASH at community level in informal settlements where the studies were conducted. Antibiotics were seen as “strong medications” and often purchased without prescription for treatment of diarrhoea, raising concerns on Anti-Microbial Resistance (AMR), while home remedies such as rice porridge were used for less severe diarrhoea symptoms. Perceived or experiential benefits and safety of previous vaccines promoted vaccine uptake in all three countries. On the other hand, limited understanding of vaccines, concerns about side effects, perceived excessive vaccination, mistrust of vaccines or suspicions of existing vaccines undermined individuals’ willingness to vaccinate children. Our results highlight that a lack of attention to socio-determinants of poor health in contexts where there are several vaccines and yet a high incidence of vaccine-preventable diseases may undermine vaccine confidence. Multi-sectoral interventions to tackle social determinants of diarrhoea and improve community understanding of vaccines are required to improve overall community health outcomes.